Stabilization of Human Multidrug Resistance Protein 4 (MRP4/ABCC4) Using Novel Solubilization Agents. (December 2019) - Hardy, David; Bill, Roslyn M.; Rothnie, Alice J.; Jawhari, Anass
Membrane proteins (MPs) are important drug discovery targets for a wide range of diseases. However, elucidating the structure and function of native MP is notoriously challenging as their original structure has to be maintained once removed from the lipid bilayer. Conventionally, detergents have been used to solubilize MP with varying degrees of success concerning MP stability. To try to address this, new, more stabilizing agents have been developed, such as calixarene-based detergents and styrene–maleic acid (SMA) copolymer. Calixarene-based detergents exhibit enhanced solubilizing and stabilizing properties compared with conventional detergents, whereas SMA is able to extract MPs with their surrounding lipids, forming a nanodisc structure. Here we report a comparative study using classical detergents, calixarene-based detergents, and SMA to assess the solubilization and stabilization of the human ABC transporter MRP4 (multidrug resistance protein 4/ABCC4). We show that both SMA and calixarene-based detergents have a higher solubility efficiency (at least 80%) than conventional detergents, and show striking overstabilization features of MRP4 (up to 70 °C) with at least 30 °C stability improvement in comparison with the best conventional detergents. These solubilizing agents were successfully used to purify aggregate-free, homogenous and stable MRP4, with sevenfold higher yield for C4C7 calixarene detergent in comparison with SMA. This work paves the way to MRP4 structural and functional investigations and illustrates once more the high value of using calixarene-based detergent or SMA as versatile and efficient tools to study MP, and eventually enable drug discovery of challenging and highly druggable targets.